2020
DOI: 10.3389/fgene.2020.00323
|View full text |Cite
|
Sign up to set email alerts
|

Asian Sand Dust Particles Increased Pneumococcal Biofilm Formation in vitro and Colonization in Human Middle Ear Epithelial Cells and Rat Middle Ear Mucosa

Abstract: Introduction: Air pollutants such as Asian sand dust (ASD) and Streptococcus pneumoniae are risk factors for otitis media (OM). In this study, we evaluate the role of ASD in pneumococcal in vitro biofilm growth and colonization on human middle ear epithelium cells (HMEECs) and rat middle ear using the rat OM model. Methods: S. pneumoniae D39 in vitro biofilm growth in the presence of ASD (50-300 µg/ml) was evaluated in metal ion-free BHI medium using CV-microplate assay, colony-forming unit (cfu) counts, resaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…Conversely, in the cell-free condition, h-ASD increased ROS production compared to vehicle, although the value was considerably lower than that of h-PM2.5 at 50 µg/mL. Previous studies have demonstrated that h-ASD exposure induces apoptosis of epithelial cells, concomitant with increased ROS production [27,28]. However, Piao et al [29] showed that exposure of human keratinocytes to PM2.5 increased intracellular ROS production, leading to endoplasmic reticulum stress, mitochondrial damage, autophagy, and cell apoptosis.…”
Section: Discussionmentioning
confidence: 92%
“…Conversely, in the cell-free condition, h-ASD increased ROS production compared to vehicle, although the value was considerably lower than that of h-PM2.5 at 50 µg/mL. Previous studies have demonstrated that h-ASD exposure induces apoptosis of epithelial cells, concomitant with increased ROS production [27,28]. However, Piao et al [29] showed that exposure of human keratinocytes to PM2.5 increased intracellular ROS production, leading to endoplasmic reticulum stress, mitochondrial damage, autophagy, and cell apoptosis.…”
Section: Discussionmentioning
confidence: 92%
“…The metallic components of ASD, such as iron, magnesium, and manganese, affect the production and metabolism of the fungal biomass [ 24 ]. The metallic components also increase the generation of pneumococcal biofilms and the colonization in middle ear epithelial cells [ 14 ]. Bacterial and fungal biofilms coexist in CRS patients, and these organisms synergistically interact to contribute to the development and survival of biofilms [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…ASD and A. fumigatus are risk factors for FB and CRS. The presence of ASD decreases host immune defense and increases cell susceptibility to bacterial infection and biofilm formation in the airway mucosa [ 14 ]. ASD particles may provide a favorable surface for fungal attachment and biofilm growth.…”
Section: Introductionmentioning
confidence: 99%
“…Biofilm-dispersing Spn exhibit aggressive growth and virulence phenotypes through their increased production of bacteriocins, virulence factors (capsule, cbpA, pspA, ply, pcpA, nanA, and nanB), proteins of unknown function (SPV_2027 and SPV_2171), and factors related to carbohydrate metabolism, while reducing the expression of genes for competence and adhesion (Gualdi et al, 2012;Allan et al, 2014;Pettigrew et al, 2014;Paixao et al, 2015a;Paixao et al, 2015b;Aprianto et al, 2018). Particle matters (i.e., Asian sand dust, cigarette smoke and black carbon source) induce biofilm formation hence Spn colonization of the human ME epithelium in cell lines and in the ME of mouse OM model (Hussey et al, 2017;Yadav et al, 2020). Genes for biofilm formation (luxS), competence (comA, comB, ciaR), toxin production (lytA and ply), detoxification, efflux pumps and osmo-regulator transporters were up-regulated during pneumococcal infection (Cockeran et al, 2014;Manna et al, 2018;Yadav et al, 2020).…”
Section: Gene Expression During Colonizationmentioning
confidence: 99%
“…Particle matters (i.e., Asian sand dust, cigarette smoke and black carbon source) induce biofilm formation hence Spn colonization of the human ME epithelium in cell lines and in the ME of mouse OM model (Hussey et al, 2017;Yadav et al, 2020). Genes for biofilm formation (luxS), competence (comA, comB, ciaR), toxin production (lytA and ply), detoxification, efflux pumps and osmo-regulator transporters were up-regulated during pneumococcal infection (Cockeran et al, 2014;Manna et al, 2018;Yadav et al, 2020).…”
Section: Gene Expression During Colonizationmentioning
confidence: 99%